Qualidade higiênico-sanitária do leite cru comercializado no município de Cuiabá - MT - Zaffalon, Gabriela Brocco (2024)
The consumption of raw milk in Brazil is a controversial topic. While Brazilian legislation establishes that all fluid milk intended for human consumption must be processed, some consumers, influenced by cultural and social factors, advocate for the consumption of raw milk, claiming potential benefits, or seeking a more affordable price, or the convenience of receiving the product at home. However, scientific research demonstrates that thermal processing, besides ensuring microbiological quality, does not significantly affect the nutritional value of milk, which remains a rich source of essential vitamins. Nevertheless, the consumption of raw milk persists among many people who, most of the time, are unaware of the risks associated with this practice. These risks include the presence of chemical, physical, and biological contaminants, as well as the possibility of pathogen transmission. To ensure the safety of milk offered to consumers, rigorous measures are necessary at all stages of the production chain, including regular inspections, compliance with legislation, adoption of good practices, and education of producers and industries. Thus, this study aimed to evaluate the hygienic-sanitary quality of raw milk marketed in the municipality of Cuiabá – Mato Grosso through physical-chemical analyses, microbiological analyses, fraud detection, and analysis of resistance to disinfectants. Forty bottles of raw milk from 4 different producers were acquired and sent to the NEPES Laboratory, at the Faculty of Agronomy and Animal Science of the Federal University of Mato Grosso, Cuiabá Campus. The samples were kept refrigerated for a maximum of 24 hours until the moment of analysis. All sample groups showed significant results for the counts of: aerobic mesophiles (10.46 Log10CFU/ml), enterobacteria (9.86 Log10CFU/ml), total coliforms (4.17 Log10MPN/ml), thermotolerant coliforms (3.34Log10 MPN/ml), and psychrotrophic microorganisms (7.71 Log10CFU/ml). No sample was positive for Salmonella spp. In the physical-chemical analyses, samples showed parameters outside the limits established by legislation: fat (15%), protein (20%), lactose (15%), defatted solids (47.5%), total solids (20%), density (20%), cryoscopic index (82.5%), and Dornic acidity (60%). Additionally, 70% of the samples showed instability to alcohol-alizarol and a pH ranging from 5.58 to 6.12. The detected frauds were water addition (30%), sucrose (7.5%), hydrogen peroxide (20%), and antimicrobial residues (7.5%). Five disinfectants were tested against the isolates, showing the following average inhibition halo for mesophiles, enterobacteria, and total coliforms respectively: "Disinfectant A" = 0mm, 0mm, and 0.6mm; "Disinfectant B" = 10.91mm, 12.33mm, and 11.71mm; "Disinfectant C" = 9.85mm, 9.42mm, and 8.38mm; "Disinfectant D" = 18.15mm, 18.76mm, and 18.9mm; "Disinfectant E" = 1.83mm, 1.47mm, and 1.72mm. The results obtained in this research are of extreme importance in the field of food safety and public health, demonstrating unhygienic manipulation, obtaining milk in a poorly or non-hygienic environment, where in addition to bacterial contamination, the presence of foreign substances could be observed, probably intentionally added to mask the poor quality of the product. All of this demonstrates unhygienic manipulation and reflects the low quality of informal milk marketed in the municipality